Academic socialization, parental educational expectations, and academic self‐efficacy among Latino adolescents. Issue 4 (15th February 2019) - Cross, Fernanda L.; Marchand, Aixa D.; Medina, Michael; Villafuerte, Andrea; Rivas‐Drake, Deborah
Abstract: This study examined the direct association between parental educational expectations and adolescents' academic self‐efficacy, as well as the moderating influence of parental academic socialization messages. Participants were 148 Latino parent–adolescent dyads with the majority of Mexican origin (80.4%). Most of the parent participants were mothers (85.8%). Adolescents were 13 (46%) or 14 (54%) years of age, and 53% identified as female. Adolescents reported their academic self‐efficacy and perceptions of their parents' educational expectations; parents reported on their academic socialization messages of shame/pressure and effort regarding academics. The results suggest that, after accounting for parents' level of education and immigrant status, parental educational expectations were positively associated with adolescent academic self‐efficacy. This association was stronger among adolescents whose parents reported transmitting fewer messages of shame/pressure and academic effort. These results point to the importance of nuances in the content and type of academic socialization messages within Latino families.